TAX AVOIDANCE IN NON-CYCLICAL CONSUMER COMPANIES REGISTERED ON THE IDX DURING 2020 - 2022 - Oktapiani, Made Putri Adelia; Wirianata, Henny (Graduate Program of Universitas Tarumanagara, 2024)
This research aims to obtain empirical evidence regarding the influence of company size, leverage and profitability on tax avoidance in non-cyclical consumer companies listed on the Indonesia Stock Exchange in 2020-2022. The total sample for this research was 48 non-cyclical companies selected using a purposive sampling method. This research uses the classic assumption test before testing the hypothesis and the multiple linear regression method. Random Effect Model is a panel data regression method that is suitable for this research. The dependent variable in this research is tax avoidance where the results obtained are that company size has no effect on tax avoidance, while leverage and profitability have a positive effect on tax avoidance. The higher the company's leverage and profitability, the higher the tax avoidance it incurs. Apart from that, this research also shows that simultaneously the independent variables, namely company size, leverage and profitability, have an effect on tax avoidance in non-cyclical consumer companies listed on the IDX during the 2020 - 2022 period.